Program Pengembangan Desa Mitra: Kelurahan Semarapura Kaja Menuju Wisata Terintegrasi - Putu Ngurah Suyatna Yasa; I Made Mardika; A. A. Rai Sita Laksmi (Postgraduated Community Service Journal, 2021)
PPDM on "Community Empowerment in Realizing Integrated Tourism in Semarapura Kaja Village, Klungkung" makes the lurah and community groups of Semarapura Kaja Village as partners and target audiences. Semarapura Kaja was chosen as the location for the service because this area is rich in tourism potential, has the support of the Klungkung Regency government, and has submitted an application to be a village under the Postgraduate Program of Warmadewa University. The purpose of PPDM is to empower the community in order to prepare, design and develop various tourism potentials they have. Program priorities concern community empowerment, environmental management, information preparation and tourism promotion. The problems faced by partners include: (1) The Pokdarwis of Smarapura Kaja Village is not yet skilled in communicating in English, (2) There is no information in the form of documents about DTW in Semarapura Kaja Village, (3) There is no public facility in the form of toilets as a means of supporting tourism, (4) The management and marketing of MSMEs in Semarapura Kaja Village has not been maximized, and (5) There is no public service innovation yet. The solutions offered are strengthening English skills for Pokdarwis, compiling tourist information brochures, procurement/development of toilets, counseling and mentoring in management and marketing management for MSMEs, training and assistance in making android-based public service applications. The results of the second year of PPDM include: (1) MSME actors have online marketing skills with social media, (2) MCK building at Tirta Celempung Temple, (3) Pokdarwis English language skills increase, (4) availability of android-based applications for processing letters , and (5) tourist information brochures are available.